Surgical Implications of the Distal Tibia Morphology at the Incisura for Glenoid Augmentation. Issue 7 (30th July 2018) - Shaw, Kenneth Aaron; Moreland, Colleen M.; Chabak, Mickey S.; Provencher, Matthew T.; Parada, Stephen
Objectives: Distal tibia allograft (DTA) glenoid augmentation has been introduced as a viable treatment approach for glenoid bone loss in conjunction with shoulder instability. An ideal graft has a flat or nearly flat lateral border of the tibia, allowing the surgeon to retain the lateral cortical bone for increased screw fixation (Figure 1A). DTA grafts with a deep concavity are difficult to prepare for fixation, as it is necessary to remove most of the cortical bone to create a flat contour of the graft (Figure 1B). Previous anatomic studies have sought to evaluate the morphology at the incisura as it pertains to syndesmosis fixation. No previous study has assessed the morphologic variation of the distal tibia at the incisura as it relates to graft dimensions for glenoid augmentation. Methods: Magnetic resonance images (MRI) of the ankle were reviewed over a 3 month period. Studies that met inclusionary criteria underwent morphology assessment to characterize the appearance and depth of the distal tibia at the incisura, both at the articular surface and the physeal scar, representing the typical depth of a DTA graft. Measurements were performed by two independent observers and inter-rater reliability was assessed. A three-part classification system was created reflecting the suitability of the distal tibial for glenoid augmentation. Type A grafts contained a flat contour of the lateral tibia, indicative of an ideal graft. Type B grafts had a slight concavity, with a central depth < 5 mm and were deemed acceptable grafts. Type C grafts had a deep concavity, with a central depth > 5 mm and were deemed unacceptable for glenoid augmentation. Statistical analysis was performed using univariate analyses to compare recorded patient demographics against acceptable morphology for glenoid augmentation. Results: 101 patients were identified with 16 excluded, leaving 85 patients for study inclusion (53 male, 32 female, average 35.1 years ±10.3 years). Overall, 12 patients (14.1%) demonstrated a type A morphology, with an additional 61 patients (71.8%) having a type B morphology for a total of 85.9% with an acceptable specimens for glenoid augmentation. The inter-rater reliability was moderate to strong between measuring observers (0.793). Only gender has found to effect the likelihood of an acceptable graft with 100% of female patients having an acceptable morphology, compared to 77% of male patients (p=0.004). Conclusion: The morphology of the distal tibia at the incisura, as it relates to glenoid augmentation was variable in this patient cohort. 14.1% of patients demonstrated an ideal morphology for glenoid augmentation, with an additional 71.8% were deemed suitable for graft usage with only minor contouring necessary. 14.1% of patients were found to have an unacceptable morphology. Gender was a significant factor for predicting acceptable grafts, with 100% of female patients having an acceptable morphology. This information will help surgeons accept or reject grafts based on the knowledge of the epidemiology of the distal tibia morphology as it relates to glenoid augmentation.